Sketching pion and proton mass distributions - Xiaobin Wang; Zanbin Xing; Lei Chang; Minghui Ding; Khépani Raya; Craig D. Roberts (Physics Letters B)
A light-front holographic model is used to illustrate an algebraic scheme for constructing a representation of a hadron's zero-skewness generalised parton distribution (GPD) from its valence-quark distribution function (DF) and electromagnetic form factor, FH, without reference to deeply virtual Compton scattering data. The hadron's mass distribution gravitational form factor, AH, calculated from this GPD is harder than FH; and, for each hadron, the associated mass-density profile is more compact than the analogous charge profile, with each pion near-core density being larger than that of its proton partner. These features are independent of the scheme employed.